2019
DOI: 10.3122/jabfm.2019.06.180323
|View full text |Cite
|
Sign up to set email alerts
|

Different Depression Treatment Recommendations and Adherence for Spanish- and English-Speaking Patients

Abstract: National guidelines recommend primary care providers (PCPs) screen patients for depression with a standardized tool and address positive screenings. However, depression prevalence is lower in Latinos (8% to 15%, with Spanish speakers at 8%) than non-Latino whites (22%). As a result of these prevalence differences, PCPs may use ethnicity and language of the patient to determine depression screening behaviors. This study examined standard of care (SoC) depression treatment recommendations by ethnicity and langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Research also finds inequitable referrals for mental health among Latinos. One study found that Spanish-speaking Latinos were 72% less likely to receive mental health referrals from primary care providers with patients’ negative perceptions about medications, patient noncompliance, and a shortage of bilingual behavioral health providers within the clinic explaining why [ 47 ]. Trans women who are undocumented may be the least likely to receive referrals and access to mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Research also finds inequitable referrals for mental health among Latinos. One study found that Spanish-speaking Latinos were 72% less likely to receive mental health referrals from primary care providers with patients’ negative perceptions about medications, patient noncompliance, and a shortage of bilingual behavioral health providers within the clinic explaining why [ 47 ]. Trans women who are undocumented may be the least likely to receive referrals and access to mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…Stephenson et al 22 examined the implementation of standard of care depression treatment recommendations by ethnicity and language for patients who screened positive for major depression during a medical visit at an Integrated Federally Qualified Health Center. Spanish-speaking Latinos were less likely to receive or follow through with standard of care recommendations compared with English-speakers regardless of ethnicity.…”
Section: Social Determinants Of Health-challenges To Best Medical Carmentioning
confidence: 99%
“…Although the prevalence rate of depression among U.S. Latinx individuals varies across epidemiological studies (e.g., Alegría et al, 2008; Menselson et al, 2008), one of the more recent epidemiologic cohort studies conducted to date suggests that the prevalence of depression among Latinx and non-Latinx, White individuals is similar (Wassertheil-Smoller et al, 2004). However, Latinx individuals, particularly those with a Spanish-speaking preference (LSSP), are less likely to receive depression care according to evidence-based guidelines relative to non-Latinx, White Americans, a pattern that persisted for decades (e.g., Blanco et al, 2007; Stephenson et al, 2019). As we continue to strive to create an ethical and equitable health system, it is imperative to target these treatment disparities and provide broader access to effective mental health care by developing and evaluating psychotherapies that address the modifiable depression care needs of this underserved U.S. population.…”
mentioning
confidence: 99%